Peningkatan Kompetensi Pembelajaran melalui Pelatihan Media dan Metode Pembelajaran pada Program Kampus Mengajar Angkatan III di SDN 002 Benai, Kuantan Singingi, Riau - Irfandi; Ikrima Mailani; Wirsa Andani; Winda Ningsih; Nur Azima; M. Rendi (Yayasan Tajuk Indonesia, 2025)
Independent Learning and Independent Campus is a program from the Ministry of Education and Culture that provides opportunities for students to learn outside the classroom and develop themselves according to their interests and talents. To help students prepare for their future careers, the independent campus aims to encourage them to master various scientific Methods used in this activity are interactive and participatory methods. This teaching campus program activity was held on September 27 – December 21. The location of the assignment is at SDN 002 Benai, Benai District, Kuantan Singingi Regency, Riau. The results of service activities while at school carried out by the 3rd batch of teaching campus students are literacy, numeracy, assessment, soft skills, current issues, national vision. This program is expected to have a positive influence on students so that they are better prepared to enter the world of work.